Motivation toward Physical Activity and Healthy Habits of Adolescents: A Systematic Review - Javier Cachón-Zagalaz; Hanrriette Carrasco-Venturelli; María Sánchez-Zafra; María Luisa Zagalaz-Sánchez (MDPI AG, 2023)
Adolescence is a transformative period in which rapid physical, cognitive and psychosocial growth takes place. Laying the foundation for healthy behaviors is paramount during these formative years. The aim of this review is to determine which countries are leading in research on adolescents' motivation towards physical activity and healthy habits and their main findings. A systematic review was conducted following the PRISMA statement using the Web of Science and Scopus databases during the months of September to December 2022. The search terms used were: "Physical activity", "Motivation" and "Adolescents", in the following research areas: Education, Educational Research and Sport Sciences. A total of 5594 articles were identified, but only those that met the established criteria were included (32 articles). It is concluded that most of the research is led in Spain with 16 articles, followed by 3 in Chile, 2 in Portugal, 2 in Norway and the rest of the countries with 1. Likewise, most of the works include very similar aspects regarding the incidence of motivation towards the adherence to the practice of Physical Activity and healthy habits.